Architecture of a Distributed Process Co‐simulation Framework. Issue 10 (16th July 2020) - Wack, Thorsten; Schröder, Andreas; Yildiz, Evren
Abstract: As part of the Carbon2Chem® joint research project, mathematical models are involved to simulate operating scenarios for cross‐industrial networks. An optimal model‐based system integration approach requires a scalable co‐simulation framework that enables the distributed development of constituent subsystems. By using a classic waveform relaxation algorithm, model suppliers and integrators can exchange co‐simulation units without having to disclose sensitive information and intellectual property. Here, the underlying IT architecture and the basic principles of the introduced "model as a service" approach are described. Abstract : The distributed development in the model‐based system integration of complex technical systems has high demands on the tools used. Flexibility, scalability, and collaboration capabilities in a multi‐user environment are just some of the important properties. The presented model‐as‐a‐service approach shows how this goal can be achieved.